The Effects of Weathering Exposure on the Physical, Mechanical, and Thermal Properties of High-density Polyethylene and Poly (Vinyl Chloride) - Lodi, Paulo Cesar [UNESP]; Bueno, Benedito de Souza; Vilar, Orencio Monje (Univ Fed Sao Carlos, Dept Engenharia Materials, 2013)
This paper presents results describing the physical, mechanical, and thermal properties (melt flow index - MFI and oxidative induction time - OIT) of high density polyethylene and poly (vinyl chloride) after weathering exposure (6, 12, 18, and 30 months). The materials exposed were geomembranes of two thicknesses: 1.0 and 2.0 mm (PVC) and 0.8 and 2.5 mm (HDPE). The climate parameters (average) obtained were 25 degrees C (temperature), 93 mm (precipitation), 66% (relative humidity), and 19 MJ/m(2). day (intensity of global radiation). Some results showed, for instance, that the behavior of the geomembranes changed after the exposures. A few minor variations in physical properties occurred. The density and thickness, for instance, varied 0.5-1.0% (average) for both the PVC and HDPE geomembranes. The mechanical properties changed as a function of the period of exposure. In general, some decreases were verified by the deformation of PVC. The samples became more rigid. In contrast, HDPE geomembranes became more ductile. Despite the variations in elasticity, some increases in deformability were verified. An MFI test showed some degradation in HDPE geomembranes. OIT tests revealed small values for both intact and exposed samples.
Keywords: HDPE and PVC geomembranes; weathering exposure; physical and mechanical properties; oxidative degradation